2021
DOI: 10.7554/elife.69601
|View full text |Cite
|
Sign up to set email alerts
|

Hsp40s play complementary roles in the prevention of tau amyloid formation

Abstract: The microtubule-associated protein, tau, is the major subunit of neurofibrillary tangles associated with neurodegenerative conditions, such as Alzheimer's disease. In the cell, however, tau aggregation can be prevented by a class of proteins known as molecular chaperones. While numerous chaperones are known to interact with tau, though, little is known regarding the mechanisms by which these prevent tau aggregation. Here, we describe the effects of ATP-independent Hsp40 chaperones, DNAJA2 and DNAJB1, on tau am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 72 publications
1
32
0
1
Order By: Relevance
“…We previously demonstrated that DNAJB8 H31Q is effective for profiling the misfoldome in response to cellular stress 20 , due to seemingly irreversible binding to its client proteins in the cell. DNAJB1 is one of the best studied Hsp40s due to its high concentration, promiscuous activity, selectivity for misfolded protein, and high similarity to yeast Sis1 15,36,46,47 , leading us to consider whether DNAJB1 could be similarly used to recover its cellular clients. We find that DNAJB1 WT preferentially associates with Hsp70 family members, pulling down a far less diverse proteome than DNAJB8 ( Figure S5 ), consistent with its primarily ATP (and presumably Hsp70)-dependent biological function.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that DNAJB8 H31Q is effective for profiling the misfoldome in response to cellular stress 20 , due to seemingly irreversible binding to its client proteins in the cell. DNAJB1 is one of the best studied Hsp40s due to its high concentration, promiscuous activity, selectivity for misfolded protein, and high similarity to yeast Sis1 15,36,46,47 , leading us to consider whether DNAJB1 could be similarly used to recover its cellular clients. We find that DNAJB1 WT preferentially associates with Hsp70 family members, pulling down a far less diverse proteome than DNAJB8 ( Figure S5 ), consistent with its primarily ATP (and presumably Hsp70)-dependent biological function.…”
Section: Discussionmentioning
confidence: 99%
“…, 2016 ). Related Hsp40s have also been found to bind in different ways to a given substrate ( Irwin et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…the minimum oligomer size not in equilibrium with the monomer. 27 Although this nucleus is often assumed to be a dimer 28, 29 , estimates range from monomers 30 to tetramers. 31 The challenge with determining the critical nucleus size from experiments like those using ThT fluorescence is that any oligomer of the critical nucleus size or higher is assumed to be fibrillar and thus observable: this assumption couples the results of the kinetic modelling to resolution limit of the experiment and may explain some of the variability seen in critical nucleus size estimates.…”
Section: Discussionmentioning
confidence: 99%